DEFERRED STATISTICAL CONVERGENCE OF ORDER ? - OMER, OMER (Fırat Üniveristesi, 2017)
Beş bölümden oluşan bu tezin ilk bölümünde konuya ilişkin bazı temel kavramlar verilmiştir. İkinci bölümde deferred istatistiksel yakınsaklık ve kuvvetli deferred Cesaro yakınsaklık incelenmiş ve bu kavramlar arasındaki ilişki verilmiştir. Üçüncü bölümde ?. dereceden istatistiksel yakınsaklık ve ?. dereceden Cesaro yakınsaklık incelenmiş ve bu kavramlar arasındaki ilişki verilmiştir. Dördüncü bölümde ?. dereceden istatistiksel sınırlılık tanımlanmış ve ?. derecedenistatistikselsınırlılıkileistatistikselsınırlılıkarasındakiilişkiverilmiştir. Son bölümde ?. dereceden deferred istatistiksel yakınsaklık ve ?. dereceden kuvvetli deferred Cesaro yakınsaklık tanımlanmış ve bu kavramlar arasındaki ilişki verilmiştir.

In the first chapter of this thesis is consisting of five chapters, some basic concepts related to the subject are given. In the second chapter, deferred statistical convergence and strong deferred Cesaro convergence are investigated and the relations between deferred statistical convergence and strong deferred Cesaro convergence are given. In the third chapter, statistical convergence of order ? and strong Cesaro convergence of order ? are examined and the relations between these concepts are given. In the fourth chapter statistical boundedness of order ? was defined and the relations between statistical boundedness of order ?. and statistical boundedness are given. In the last chapter deferred statistical convergence of order ?. and strong deferred Cesaro convergence of order ?. were defined and the relations between these concepts are given.
?. dereceden gecikmeli istatistiksel yakınsaklık
Keywords: Matematik